A Symmetric Key based Secret Data Sharing Scheme - Bhowmik, Anirban; Sarkar, Arindam; Karforma, Sunil; Dey, Joydeep (International Journal of Computer Sciences and Engineering, 2025)
Data security over the Internet communication is the prime concern in this technological fast era. One of the major and fruitful security techniques is data encryption with keys. The efficiency of the encryption depends on the resistance ability of the encryption key. This paper presents an attack resistant symmetric key encryption model. In this paper, the threshold cryptographic technique provides a reliable and robust key and cipher text management system. The novelty of this system is it reconstructs the key and cipher text even in the case of destruction of difference between total shares and threshold shares on the contrary end. Thus secret sharing with symmetric key provides a robust encryption technique. The implemented symmetric key is the unique group symmetric key. The existing techniques available in world lead to high computational complexity during both sharing and reconstructing of plain text. A proposed masking method, share generation using that mask and transmission has been deployed. The symmetric key is used to impose proposed authenticity of data by implementation of the proposed key expansion technique. A secret sharing technique along with conventional cryptography technique for symmetric key validation and management make this methodology more robust. Statistical type of test results proves the robustness of our technique.